Bless your heart - Ryan, Lindy (Bless your heart, 2024)
"Rise and shine. The Evans women have some undead to kill. It's 1999 in Southeast Texas and the Evans women, owners of the only funeral parlor in town, are keeping steady with...normal business. The dead die, you bury them. End of story. That's how Ducey Evans has done it for the last eighty years, and her progeny--Lenore the experimenter and Grace, Lenore's soft-hearted daughter, have run Evans Funeral Parlor for the last fifteen years without drama. Ever since That Godawful Mess that left two bodies in the ground and Grace raising her infant daughter Luna, alone. But when town gossip Mina Jean Murphy's body is brought in for a regular burial and she rises from the dead instead, it's clear that the Strigoi--the original vampire--are back. And the Evans women are the ones who need to fight back to protect their town. As more folks in town turn up dead and Deputy Roger Taylor begins asking way too many questions, Ducey, Lenore, Grace, and now Luna, must take up their blades and figure out who is behind the Strigoi's return. As the saying goes, what rises up, must go back down. But as unspoken secrets and revelations spill from the past into the present, the Evans family must face that sometimes, the dead aren't the only things you want to keep buried."--